POLA PRODUKSI AJMALISIN DARIKULTUR AGREGAT SEL Catharanthus roseus (L) G Don. DALAM BIOREAKTOR - Aida Muspiah; Rizkita Rahmi Esyanti; Arbayah H Siregar; Erman Tritama (BERITA BIOLOGI, 2002)
A research has been conducted to optimize the rate of aeration and initial cell aggregates weight in the production of ajmalicine in Catharanthus roseus cell culture in bioreactor. Catharanthus roseus culture were grown in Zenk medium with the addition of 2.5 x 10"6 M NAA ('naphthalene acetic acid') and 10s M BAP ('benzyl amino purine'). Cell aggregates were subcultured two times before transferring 20 and 30 g/fw of cell aggregates into bioreactor, respectively, and aerated with the rate of 0.2460 L/min and 0,3405 L/min, respectively. The pattern of ajmalicine production in bioreactor were observed every 3 days for 24 days.Qualitative and quantitative analysis were conducted using HPLC connected to Cromatopac CL-7APlus. The results showed that the cell aggregates and medium contain ajmalicine. The highest concentration was obtained in combination of 30 g/fw and 0.3405 L/min aeration compare to 20 g/fw - 0,246 L/min, 20 g/fw- 0,3405 L/min, as well as 30 g/fw - 0,2460 L/min. The highest ajmalicine content in cell aggregates was obtained on the 12"d days (79.23ug/g) whilst in medium was obtained in the 18th days (981.15 ug/L).